2017
DOI: 10.1332/174426416x14534671325644
|View full text |Cite
|
Sign up to set email alerts
|

Missing in action? The role of the knowledge mobilisation literature in developing knowledge mobilisation practices

Abstract: Despite a burgeoning literature and the development of new theories about knowledge mobilisation in the past fifteen years, findings from this online survey in 2014 of over 100 research agencies (n=106; response rate 57%) show the challenges of making effective use of formal and informal learning. Many agencies rely on traditional knowledge 'push' activities; formal use of theoretical models and frameworks is patchy; and knowledge-sharing between agencies and the comprehensive evaluation of knowledge mobilisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…I also have a better plan of action to improve KMb practice on campus." Notwithstanding similar evidence of growth, a divide between developments in KMb theory and practice was noted (FL), echoing other recent studies of KMb in research organizations (e.g., Powell, Davies, & Nutley, 2017. Specifically, while members extolled their "greater understanding of KMb in the university setting," they were less certain about improvements in their understanding of KMb theory.…”
Section: Usefulness Of a Networked Approach To Building Institutionalsupporting
confidence: 54%
“…I also have a better plan of action to improve KMb practice on campus." Notwithstanding similar evidence of growth, a divide between developments in KMb theory and practice was noted (FL), echoing other recent studies of KMb in research organizations (e.g., Powell, Davies, & Nutley, 2017. Specifically, while members extolled their "greater understanding of KMb in the university setting," they were less certain about improvements in their understanding of KMb theory.…”
Section: Usefulness Of a Networked Approach To Building Institutionalsupporting
confidence: 54%
“…The limitations of the knowledge mobilization literature—for example, the limited number of empirical studies on major models and frameworks and on approaches in use—have been widely discussed (e.g., Ferlie et al ). However, our own review of major reviews published in the period 2000–15 (Davies et al ) and our survey work with research agencies (Powell et al ) showed that there are a growing number of key principles, underpinned by research evidence and finding widespread support, that can be used to inform the development of knowledge mobilization activities.…”
Section: Background: What Does the Knowledge Mobilization Literature mentioning
confidence: 97%
“…However, our own review of major reviews published in the period 2000-15 and our survey work with research agencies (Powell et al 2016) showed that there are a growing number of key principles, underpinned by research evidence and finding widespread support, that can be used to inform the development of knowledge mobilization activities.…”
Section: Background: What Does the Knowledge Mobilization Literaturmentioning
confidence: 99%
“…Impact includes not only the context of research use but research production and, ultimately, the connections among production and use. While faculty and practitioners in the education sector already interact in various ways, the use of research outside of disciplinary communities is typically slow, intermittent, and inadequate (Powell, Davies, & Nutley, 2017). Faculty and practitioners therefore often interact only indirectly via passive, discrete, and one-way dissemination strategies such as traditional journal publications or policy briefs.…”
Section: Introductionmentioning
confidence: 99%